2015
DOI: 10.1063/1.4919623
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of one-dimensional self-organized pattern in an atmospheric-pressure dielectric barrier discharge

Abstract: A two-dimensional fluid model is developed to simulate the one-dimensional self-organized patterns in an atmospheric-pressure dielectric barrier discharge (DBD) driven by sinusoidal voltage in argon. Under certain conditions, by changing applied voltage amplitude, the transversely uniform discharge can evolve into the patterned discharge and the varied self-organized patterned discharges with different numbers and arrangements of discharge channels can be observed. Similar to the uniform atmospheric-pressure D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
4
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
(30 reference statements)
6
4
0
1
Order By: Relevance
“…These discussions are basically in good agreement with the results and considerations of Ouyang's group [51,52,59]. Wang et al [62] also agreed that the reason for the formation of glow DBD pattern is due to the activationinhibition mechanism resulting from high-density space charge.…”
Section: Theoretical Approachessupporting
confidence: 87%
See 1 more Smart Citation
“…These discussions are basically in good agreement with the results and considerations of Ouyang's group [51,52,59]. Wang et al [62] also agreed that the reason for the formation of glow DBD pattern is due to the activationinhibition mechanism resulting from high-density space charge.…”
Section: Theoretical Approachessupporting
confidence: 87%
“…The first fluid simulation on DBD patterns came from Boeuf and co-workers [42,56]. After that, several spatial patterns or complex structures such as hexagons have been reproduced successfully by using similar two-dimensional [35,[57][58][59][60][61][62] or three-dimensional fluid models [63,64]. The common proposal for the cause of pattern formation relies on the surface charges.…”
Section: Theoretical Approachesmentioning
confidence: 99%
“…By experimentally increasing the amplitude (V am ) of the applied voltage, Guikema et al [14] observed that the discharge structure would transform from the filamentary mode to the relatively diffuse mode in a He-Ar DBD. The similar trans ition process was also reported by Zhang et al [15] in a pure Ar DBD and by Hao et al [16] in a pure He DBD. Additionally, through plasma fluid simulations, Zhang et al [17] found a similar transition of the discharge uniformity in a He (with N 2 as impurities) DBD when changing the driving frequency (f ).…”
Section: Introductionsupporting
confidence: 88%
“…Therefore, two questions naturally arise: why do the solitary filaments form and how can we achieve a HDBD? Many previous reports have focused on these two aspects [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…As a significant tool, the numerical simulation has attracted increasing attention in recent years. Substantial efforts have been made for fluid-based simulations, which successfully explain the elementary properties of the discharge [7][8][9][10][11][12][13]. These models are generally based on a macroscopic description of electron and ion kinetics, in which a Maxwellian distribution of the velocities of the charged particles is assumed.…”
Section: Introductionmentioning
confidence: 99%